Profit or less waste? Digitainability in SMEs - a comparison of Hungarian and Slovakian SMEs - Saáry, Réka; Kárpáti-Daróczi, Judit; Tick, Andrea (Serbian Journal of Management, 2022)
SMEs operating in the 21st century must face several challenges including a push towards digital transformation, reorganising business operations to maintain sustainability but on the other hand not to lose profit and keep the business running. This paper aims to reveal whether the profit and the high rate of digitalisation or the sustainability concerns are the main driving forces of SMEs in Hungary and Slovakia. The paper analyses 210 observed SMEs and uses the CHAID decision tree method parallel to factor and cluster analyses to explore the similarities and differences in Hungarian and Slovakian SME behaviours. The results show Slovakian SMEs have a more positive attitude to digitalisation; both Hungarian and Slovakian SMEs are split into two groups in terms of approach to digitalisation and sustainability while the significant differences vary provided the questions of cost and resource reduction, extension of product life cycle or higher productivity are concerned. SMES in both countries agree that business models need to be adjusted to digitalisation and sustainability while they are concerned about the negative impact of digitalisation although significantly differently.